Ins and outs of cadmium-induced carcinogenesis: Mechanism and prevention. (2021) - Cui, Zheng-Guo; Ahmed, Kanwal; Zaidi, Syed Faisal; Muhammad, Jibran Sualeh
Highlights: Cadmium (Cd), a toxic environmental pollutant, have numerous undesirable effects on human health. Reactive oxygen species (ROS) often play an important role in acute Cd poisoning. Cd induces epigenetic changes by altering signaling events upstream of DNA repair and apoptosis. In Cd transformed cells, tolerance to apoptosis leads to tumorigenesis. Flavonoids have a protective effect against Cd toxicity. Abstract: Cadmium (Cd) is a heavy metal and a highly toxic pollutant that is released into the environment as a byproduct of most modern factories and industries. Cd enters our body in significant quantities from contaminated water, cigarette smoke, or food product to many detrimental health hazards. Based on causal association all the Cd-related or derived compounds have been classified as carcinogens. In this study, we present an overview of the published literature to understand the molecular mechanisms for Cd-induced carcinogenesis and its prevention. In acute Cd poisoning production of reactive oxygen species is a key factor. However, chronic Cd exposure can transform cells to become more resistant to oxidative stress. Also, as an epigenetic mechanism Cd acts indirectly on DNA repair mechanisms via alteration of reactions upstream. Those transformed cells acquire resistance to apoptosis and deregulation of calcium homeostasis. Leading to uncontrolled carcinogenic cell proliferation and inherent DNA lesions. Flavonoids commonly found in plant foods have been shown to have a protective effect against Cd-induced carcinogenicity. A wide variety of tumorigenic mechanisms involved in chronic Cd exposure and the beneficial effects of flavonoids against Cd-induced carcinogenicity necessitate further investigations.